A Serious Game for Education about Oral Health in Babies. - Liliane dos Santos Machado; Ana Maria Godim Valença; Alana Marques Morais (Universidade de Brasília, 2016)
The serious games have been highlighted by the addition of playful aspects to the educational process, motivating and assisting learning through games. In this context, the game intelligence, comprised from decision models, consists of challenging and motivating element for the player. For the present study, it was observed that basic concepts related to health and oral hygiene predominate in serious games for Dentistry and children are the main target audience of these games. The shortage in exploring games with the theme oral health for infant was the focus of the development of a serious game addressed to this theme. The design of the game "Uma Aventura na Floresta da Dentolândia" (An Adventure in the Toothland Forest) allowed verifying the necessity of consider the theme and the target public in the development process of serious games. The research also allowed verifying a wide range of possibilities for the application of serious games in health.